Wie die Made im Speck? Fredsbesættelsen 1940-1943 belyst gennem samarbejdet mellem Esbjerg politi og værnemagten - Jensen, Mona (Historisk Tidsskrift, 2013)
Wie die Made im Speck? The Peaceful Occupation of Denmark 1940-1943 Seen in the Light of Cooperation Between the Police in Esbjerg and the Wehrmacht »Sie fühlten sich wie die Made im Speck,« wrote the head of the Gestapo in Esbjerg of the German troops in the town. Danish historians of the German occupation of Denmark have also noted the comfortable life that the peculiar occupation regime in Denmark afforded the Wehrmacht compared to conditions in other occupied countries. The present article provides a more complex picture of the Wehrmacht’s situation on the so-called »whip cream front.« It focuses on conditions from the viewpoint of the German authorities charged with administering the occupation regime at both the local and national levels in cooperation with the Danish authorities. The main source for depicting these conditions is internal German correspondence, especially confidential messages to and from the commander of the German troops in Denmark, General Erich Lüdke. Some of these documents, used here for the first time, are essential for understanding how the so-called peaceful occupation was experienced and managed by the German authorities charged with its implementation. Since maintenance of law and order on the part of both occupier and occupied was crucial to the occupation regime, their cooperation is also assessed from a contemporary Danish viewpoint, namely, as it was experienced by the chief constable of Esbjerg, Børge Hebo. It was his task, whenever German interests were involved, to solve police problems together with the local German commander. It was paramount for the Danish government to keep legal jurisdiction in Danish hands. The police, therefore, played an essential, yet vulnerable role, since assurance of law and order was the very basis of the peace occupation. The abilities of Esbjerg’s chief constable to negotiate and mediate between the German military and the population were put to the test shortly after the beginning of the occupation. Because of its strategic importance throughout the war the town was filled with a large number of German troops, resulting almost immediately in brawls with the male population. For the first few months the cooperative effort to keep things calm ran smoothly, but then it became increasingly marked by complaints on the part of the German commander about the hostile behaviour of the population. The commander found in Hebo an intrepid counterpart who managed to manoeuvre deftly within the confines of the occupation rules, evidencing considerable virtuosity in exploiting any lack of clarity regarding police jurisdiction. He was able to perform his function as intermediary between the occupation forces and the population without losing the trust of the latter through concessions to the former. Complaints about the inadequacy of his measures in dealing with the people of Esbjerg were frequently lodged with the negotiators at the national level. Because of the German personnel problem and the lack of clarity in the agreement on police cooperation the Danish police had authority vis-à-vis the Wehrmacht that would seem incompatible with the relation of occupied to occupier. This is a factor that helps to understand how Hebo managed. A circumstance that facilitated his task was the attitude of Esbjerg’s commander, who compared to commanders in other towns seems to have developed a greater appreciation of the importance of maintaining peaceful conditions and dependence on the efforts of the Danish police. It is probable that in Esbjerg as in other places of strategic importance the Germans had assigned a commander who understood Danish conditions. Like Esbjerg’s commander the military commander at the national level, Erich Lüdke, endeavoured to uphold amicable cooperative relations and preserve the status quo. The German plenipotentiary ( Reichsbevollmächtigter ) Renthe-Fink supported this policy and what it entailed in the way of futile efforts to enforce internal discipline. There was clearly considerable uncertainty in some segments of the military about how to play the role of peaceful occupier, resulting among other things in persistent Danish complaints, thus weakening the bargaining position of the German authorities. The German negotiators let the Danish authorities understand that they were strongly dissatisfied with the efforts of the police, while in communications with Berlin there was praise for Danish efforts along with futile attempts to call attention to problems caused by internal conflicts over jurisdiction, rivalries, and irresponsibility among the occupation authorities. In acknowledgment of the problems with the troops Berlin was presented with arguments for extending the jurisdiction of the Danish police over members of the Wehrmacht. The Reich authorities, however, were deaf to these arguments, and the foundation of the peaceful occupational regime gradually eroded. A crucial problem in maintaining stability was the lack of unified German policy ( Einheitlichkeit ), creating a difficult situation for the Germans in charge of negotiations. The lack of a common attitude and uniform conduct sprang in part from disagreements on jurisdiction between competing authorities in the German hierarchy. The chain of command was apparently so unclear that all those involved seemed to define their own rules of cooperation with the Danish authorities. Both the air force and the navy created obstacles to the endeavours of Lüdke, Renthe-Fink, and the latter’s successor Werner Best to coordinate, improve, and impose discipline on the German effort to preserve the peaceful occupation. Nor was there much evidence of ability or will on the part of the highest authorities in Berlin to see the advantages for Germany of upholding the status quo. By September 1943 German confidence in the ability and will of the Danish police to solve cases of sabotage, spying, and destabilizing activity was gone, and the Gestapo took over. The agreement, which the Danish Government under protest had concluded with the German occupation force to guarantee the safety of military personnel in return for not infringing on the sovereignty and neutrality of the Danish state, was now broken by both parties. Seen through the eyes of German soldiers assignment to occupied Denmark may well have felt like »die Made im Speck,« but for the Germans in charge of negotiations the mission was marked by a futile struggle within their own camp to explain and reach consensus on how to play that odd game with no clear rules inaugurated by the peculiar conditions of a regime of peaceful occupation. Translated by Michael Wolfe